Alcohol and drug intake pattern among truckers of Haryana, India - Punia, Mehar S.; Punia, Anita; ., Anish; ., Mayank; ., Sanjeet; Jha, Sanjay K.; ., Babita (International Journal Of Community Medicine And Public Health, 2020)
Background: Use of psychoactive substances by truckers is a common occurrence globally. Truckers have been the objects of a great deal of attention for their high-risk behaviour. Intake of drugs and alcohol by truckers is closely interlinked with high risk sex behaviour. Thus, the present study was pursued to know drug and alcohol consumption pattern. Methods: Cross-sectional study among truckers for more than a year in occupation, aged 18 years and above having residence/operating base in Haryana. Sample of 4000 truckers, 1000 from each from four administrative divisions of Haryana, was taken. Results: About three fourth truckers (77%) were less than 40 years. More than half of truckers (53.2%) consumed alcohol. Only 0.4% truckers confessed of using injectable drugs during last 12 months. 14.9% of truckers confessed of using non-injectable drugs. Ganja, Bhurki and Affim were some of the commonly consumed drugs. Conclusions: Majority truckers (53.2%) consumed alcohol. Drug intake was comparatively less common (14.9%). Injectables were used the least. Directly proportional association of alcohol and drug intake with age, duration of job, non-veg diet among truckers primarily indicated as consequences of long, lonely and harsh occupational conditions. Hence, comprehensive interventions including, improvement in road conditions, entertainment and health facility at halt places, stringent driving license terms and conditions to ensure professional competency and better wages to make truckers life worth living. This will also make them amenable to health education promoting healthy and risk-free behavior among them.